Considering Interest and Action: Analyzing Types of Questions Explored by Researcher-Practitioner Partnerships. (November 2017) - Thompson, Karen D.; Martinez, Martha I.; Clinton, Chelsea; Díaz, Guadalupe
Researcher-practitioner partnerships have gained increasing prominence within education in recent years, yet scholarship on partnerships and tools to guide partnerships' work remain in their infancy. Drawing on our own work in a partnership as well as analysis of abstracts for the 41 partnerships funded by the Institute of Education Sciences and the Spencer Foundation, we analyze the prevalence of four types of research questions—data quality, information gathering, evaluation, and design questions—within partnerships and reflect on the constraints and affordances of each question type for partnerships. We argue that explicitly considering the extent to which possible questions are of high interest and are actionable for both researchers and practitioners may increase the likelihood that the needs of both parties will be met and that partnerships can truly serve as a tool for meaningful improvement in education.